Learning management system instrument development based on Aiken’s V technique - Ahmad, Nor Azlan; Mayouf, Alanazi Abdulaziz; Elias, Nur Fazidah; Mohamed, Hazura (International Journal of Evaluation and Research in Education (IJERE), 2024)
The use of the learning management system (LMS) at the Malaysian Polytechnic is constantly changing according to the current situation. In addition, the relatively low acceptance of LMS in technical and vocational education training (TVET) institutions requires further study. This paper will discuss accurate construct of measurement for LMS TVET using expert consensus through Aiken's V analysis. Based on the analysis coefficient and the reliability of the content, several important constructs have been identified involving system quality, information quality, service quality, motivation, user satisfaction, intention-to-use, self-discipline, practical training, and actual use. Through quantitative analysis, every item in constructs is calculated and reviewed by an expert in order to validate the items. The minimum validity value accepted in this study is 0.75 based on Aiken's V table, thus, two items were rejected. These items were rejected due to the same meaning and being inappropriate. This study proves the instrument's content validity based on expert agreement using the Aiken agreement index. This study contributes to a suitable instrument for measuring LMS in TVET for use in subsequent studies.